(untitled) (The Planet, 2023)
Introduction: Suicide is an important global cause of mortality. This long-term social issue is one of the major causes of unnatural death in Bangladesh, getting little attention.About one million people die each year by suicide over the world with a global mortality rate of 16 per 100,000 and 39.6 per 100,000 in Bangladesh. Poisoning has been found as the most frequent method of suicide. Objectives:This study has been conducted to show a demographic distribution on suicide events, its associated factors and some prevention strategies in Barishal district of Bangladesh. Methods & material: It is a cross sectional study which was conducted in the department of Forensic Medicine & Toxicology, Sher-E-Bangla Medical College, Barishal, Bangladesh from 1stJanuary to 31stDecember, 2021. We collected data from a total of 244 dead bodies of suicide victims, which were brought in the department of forensic Medicine & Toxicology at Sher-E-Bangla Medical College,Barishal,Bangladesh for postmortem examination. We explored the way of suicide,sex,age,profession,religious status & corresponding region of the suicidal incidences. Results: The most common mode of suicide were poisoning ( 52%) followed by hanging (48%).The most prevalent age group is age under 40 years, the rate of suicide among children is also increasing. and more women commits suicide than men. Conclusion: Young house wives, students, teenagers & poor farmers were found more prone to commit suicide & it is an underrated public health problem in Bangladesh. Establishment of national suicide surveillance is now a day’s time demanding step.